'It Is Not My Fault That You Are Jewish!': Jews, Czechs, and the Memory of the Holocaust in Film, 1949–2009. Issue 2 (3rd May 2016) - Lichtenstein, Tatjana
Abstract : This article examines the ways in which Czech filmmakers have shaped the memory of the Holocaust in the Bohemian lands. It does so through an analysis of four films: Distant Journey (1949), Romeo, Juliet, and Darkness (1959), The Death of Beautiful Deer (1986), and Protector (2009). The narratives of all of these films center on a mixed couple or an intermarried family, a site where the fate of Jews and non-Jews intersected during the Holocaust. These films thus constitute productive sites for the investigation of the representation of Jews and non-Jews' relations during the war. I argue that in the immediate postwar period, filmmakers asked probing and difficult questions about Czech complicity and defiance under German occupation. Before long, however, the mixed couple became a staging ground for narratives that privileged Czech victimization and used references to the Holocaust primarily to allude to German genocidal intent against Czechs. As such, the Jewish experience was marginalized as a historical event in favor of the 'real' Czech history of the war. Analyzing the films as manifestations of historical memory, I show that these narratives serve not only to silence Czech complicity in the social death of Jews during the war, but also to legitimize the violent un-mixing of German- and Czech-speakers after World War II. This narrative of parallel victimization of Jews and Czechs was first developed in the immediate aftermath of the war, and despite the monumental political changes experienced by the country, it has become entrenched in Czech historical memory until today.